EGCG improve meat quality, restore lipid metabolism disorder and regulate intestinal flora in high-fat fed broilers - Lujia Gao; Chen Liu; Jiaqi Wu; Ying Cui; Man Zhang; Chongpeng Bi; Anshan Shan; Xiujing Dou (Poultry Science)
Excessive oil addition can easily result in decreased disease resistance in broilers, a drop in meat quality, and disorders of glucose and lipid metabolism. Epigallocatechin gallate (EGCG) is an important bioactive component of tea and has been shown to have promising effects on the metabolism of nutrients. This study was aimed at investigating the impact of EGCG supplementation through a high-fat diet (HFD) on production performance, meat quality, lipid metabolism and the influence of intestinal flora in broiler chickens. During the experimental phase, the broilers were segregated into three groups and provided with distinct diets: a basal diet, a high-fat diet, and a high-fat diet supplemented with EGCG, respectively. The results showed that EGCG increased lightness (L*) 24 h (P < 0.05), and decreased drip loss (P < 0.05) of chicken meat; Enhanced the presence of non-essential and flavor amino acids in muscle tissue and greatly enhanced the antioxidant capacity of broilers, leading to a noteworthy upregulation of antioxidant genes at the genetic level (P < 0.05); Reduced in blood lipids, blood glucose, liver and abdominal fat accumulation in high-fat diet-induced obese chickens (P < 0.05), markedly improved serum and liver biochemical parameters, and histological analysis results also demonstrated that EGCG markedly decreased hepatic lipid accumulation caused by HFD feeding. Compared to high-fat diet-induced obese chickens, supplementation of EGCG significantly lowered hepatic fatty acid synthase (FAS) expression and lipid synthesis metabolites, while fatty acid decomposition enzymes showed no significant changes. Furthermore, EGCG significantly decreased inflammation levels and oxidative damage in high-fat diet-induced obese chickens (P < 0.05). 16S rRNA gene sequencing revealed that dietary supplementation of EGCG reduced the abundance of Bacteroidota and Dielma, while increasing the abundance of Firmicutes, Turiciactor, Romboutsia, and Parasutterella, thereby modulating the microbial composition. Dietary EGCG may have induced some of the alterations due to increased activity of the enzymes catalase (CAT) and superoxide dismutase (SOD), as well as decreased oxidation of proteins and lipids. Collectively, EGCG shows potential as an effective dietary additive for improving the high fat feeding of broiler health, feed nutrient utilization, and meat quality and nutritional value. This experiment provides a powerful new idea for the efficient utilization of oil feed and has important theoretical significance.